2022
DOI: 10.3390/ijms23031264
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Insulin Resistance: A Review of the Underlying Mechanisms behind Changes in GLUT4-Mediated Glucose Transport

Abstract: Metformin is the most commonly used treatment to increase insulin sensitivity in insulin-resistant (IR) conditions such as diabetes, prediabetes, polycystic ovary syndrome, and obesity. There is a well-documented correlation between glucose transporter 4 (GLUT4) expression and the level of IR. Therefore, the observed increase in peripheral glucose utilization after metformin treatment most likely comes from the induction of GLUT4 expression and its increased translocation to the plasma membrane. However, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 154 publications
(225 reference statements)
4
54
0
5
Order By: Relevance
“…Several studies have confirmed the IR in skeletal muscle is the initial defect in T2DM that may appear decades before β-cell dysfunction and significant hyperglycemia development ( DeFronzo and Tripathy, 2009 ; Merz and Thurmond, 2020 ). Accumulating evidence suggests that glucose transporter 4 (GLUT4) is the rate-limiting step of glucose uptake in skeletal muscle cells, and the impaired GLUT4 translocation is the principal defect of IR in skeletal muscle ( Richter and Hargreaves, 2013 ; Sanvee et al, 2019 ; Herman et al, 2022 ). Several classic pathways have been found to be involved in the translocation mechanism of GLUT4, such as phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT) signaling pathway, adenosine monophosphate-activated protein kinase (AMPK) signaling pathway, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the IR in skeletal muscle is the initial defect in T2DM that may appear decades before β-cell dysfunction and significant hyperglycemia development ( DeFronzo and Tripathy, 2009 ; Merz and Thurmond, 2020 ). Accumulating evidence suggests that glucose transporter 4 (GLUT4) is the rate-limiting step of glucose uptake in skeletal muscle cells, and the impaired GLUT4 translocation is the principal defect of IR in skeletal muscle ( Richter and Hargreaves, 2013 ; Sanvee et al, 2019 ; Herman et al, 2022 ). Several classic pathways have been found to be involved in the translocation mechanism of GLUT4, such as phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT) signaling pathway, adenosine monophosphate-activated protein kinase (AMPK) signaling pathway, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a 2 mM dose of napin-derived oligopeptides was used primarily to elucidate the possible mechanisms of their protective effects against IR and oxidative stress in the IR-HepG2 cells. Recent studies reported that glucose consumption has been tightly related to GLUT4 on the plasma membrane, and glucose fails to freely enter cells through the lipid bilayer structure of the plasma membrane without GLUT4. , Therefore, it is necessary to investigate whether oligopeptides significantly increase GLUT4 expression and translocation in vitro or in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that glucose consumption has been tightly related to GLUT4 on the plasma membrane, and glucose fails to freely enter cells through the lipid bilayer structure of the plasma membrane without GLUT4. 45,46 Therefore, it is necessary to investigate whether oligopeptides significantly increase GLUT4 expression and translocation in vitro or in vivo.…”
Section: Glucose Consumption In Ir-hepg2mentioning
confidence: 99%
“…GLUT1 was not changed after G6PD knock-down or over-expression (Figure 2e,f). GLUT4 is an insulin sensitive glucose transporter, and it transports from being intracellular to the cell surface under insulin stimulation [19][20][21]. The positive effect of G6PD deficiency on GLUT4 expression indicates its potential role in insulin signaling.…”
Section: The Role Of G6pd Deficiency In Skeletal Muscle Developmentmentioning
confidence: 99%